PENGAJARAN KRITIK SASTRA FEMINIS (FEMINIST LITERARY CRITICISM) GUNA MENINGKATKAN KESADARAN AKAN KESETARAAN GENDER PADA GENERASI MUDA - Irawan, Nafdi; Afriana , Afriana; Mubarak , Zia Hisni (ASOSIASI IDEBAHASA KEPRI, 2025)
This community service aims to improve understanding of gender equality in the younger generation by providing teaching about feminist literary criticism studies. The conception of gender is the root to the discrimination of gender. Gender discrimination is a kind of treatment that limit the basic of human rights, especially women, in social, political, economic, cultural and other aspects. Gender discrimination is a global and national issue. To achieve gender equality in society, an attempt is needed to instill the understanding and awareness of gender equality to the young generation. A feminist literary criticism provides insight into gender inequality as a social construction highlighting the role of literature in representing gender differences that can strengthen, support, and improve the understanding of gender equality. Community service activity target high school students and were conducted at SMA Gurindam Boarding School Batam. The method used is socialization with a face to face approach for three meetings. The results of the activity showed an increase in participants' understanding of the principles of feminism, being able to understand gender construction as a socio-cultural phenomenon, and awareness of gender equality, as well as a reflective attitude towards gender issues. This activity not only serves as a means of increasing cultural literacy, but also as a strategic step in forming the young generations who are aware of gender equality, gender justice, and has critical thinking.